Corrigendum to “Biotechnological valorisation of Spent Automotive Catalytic Converters: Marine microorganisms in PGE leaching and recovery” [J. Environ. Chem. Eng. 13(5) (2025) 118729] - L. Vitale; P. Tedesco; C. Galasso; G.A. Vitale; G. Varola; G. Della Sala; F. Palma Esposito; S. Balzano; J. Ghani; D. de Pascale; E. Dinelli; T.C. Meisel; et al. (Journal of Environmental Chemical Engineering, 2026)

Biotechnological valorisation of Spent Automotive Catalytic Converters: Marine microorganisms in PGE leaching and recovery - L. Vitale; P. Tedesco; C. Galasso; G.A. Vitale; G. Varola; G. Della Sala; F. Palma Esposito; S. Balzano; J. Ghani; D. de Pascale; E. Dinelli; T.C. Meisel; et al. (Journal of Environmental Chemical Engineering, 2025)

Comparative analysis of animal lifespan - Nicole C. Riddle; Peggy R. Biga; Anne M. Bronikowski; James R. Walters; Gerald S. Wilkinson; Jingyue Ellie Duan; Anthony Gamble; Erica Larschan; Richard P. Meisel; Ritambhara Singh; Ashley Webb (GeroScience, 2023)
Comparative studies of aging are a promising approach to identifying general properties of and processes leading to aging. While to date, many comparative studies of aging in animals have focused on relatively narrow species groups, methodological innovations now allow for studies that include evolutionary distant species. However, comparative studies of aging across a wide range of species that have distinct life histories introduce additional challenges in experimental design. Here, we discuss these challenges, highlight the most pressing problems that need to be solved, and provide suggestions based on current approaches to successfully carry out comparative aging studies across the animal kingdom.

Temperature‐dependent effects of house fly proto‐Y chromosomes on gene expression could be responsible for fitness differences that maintain polygenic sex determination - Kiran Adhikari; Jae Hak Son; Anna H. Rensink; Jaweria Jaweria; Daniel Bopp; Leo W. Beukeboom; Richard P. Meisel (Molecular Ecology, 2021)
Sex determination, the developmental process by which sexually dimorphic phenotypes are established, evolves fast. Evolutionary turnover in a sex determination pathway may occur via selection on alleles that are genetically linked to a new master sex determining locus on a newly formed proto‐sex chromosome. Species with polygenic sex determination, in which master regulatory genes are found on multiple different proto‐sex chromosomes, are informative models to study the evolution of sex determination and sex chromosomes. House flies are such a model system, with male determining loci possible on all six chromosomes and a female‐determiner on one of the chromosomes as well. The two most common male‐determining proto‐Y chromosomes form latitudinal clines on multiple continents, suggesting that temperature variation is an important selection pressure responsible for maintaining polygenic sex determination in this species. Temperature‐dependent fitness effects could be manifested through temperature‐dependent gene expression differences across proto‐Y chromosome genotypes. These gene expression differences may be the result of cis regulatory variants that affect the expression of genes on the proto‐sex chromosomes, or trans effects of the proto‐Y chromosomes on genes elswhere in the genome. We used RNA‐seq to identify genes whose expression depends on proto‐Y chromosome genotype and temperature in adult male house flies. We found no evidence for ecologically meaningful temperature‐dependent expression differences of sex determining genes between male genotypes, but we were probably not sampling an appropriate developmental time‐point to identify such effects. In contrast, we identified many other genes whose expression depends on the interaction between proto‐Y chromosome genotype and temperature, including genes that encode proteins involved in reproduction, metabolism, lifespan, stress response, and immunity. Notably, genes with genotype‐by‐temperature interactions on expression were not enriched on the proto‐sex chromosomes. Moreover, there was no evidence that temperature‐dependent expression is driven by chromosome‐wide cis ‐regulatory divergence between the proto‐Y and proto‐X alleles. Therefore, if temperature‐dependent gene expression is responsible for differences in phenotypes and fitness of proto‐Y genotypes across house fly populations, these effects are driven by a small number of temperature‐dependent alleles on the proto‐Y chromosomes that may have trans effects on the expression of genes on other chromosomes.

Sexual conflict and the maintenance of genetic variation in natural populations - Richard P. Meisel (Molecular Ecology, 2018)
Understanding the factors that maintain genetic variation in natural populations is a foundational goal of evolutionary biology. To this end, population geneticists have developed a variety of models that can produce stable polymorphisms. In one of the earliest models, Owen ( ) demonstrated that differences in selection pressures acting on males and females could maintain multiple alleles of a gene at a stable equilibrium. If the selection pressures act in opposite directions in males and females, we refer to this as (inter‐) sexual conflict or sexual antagonism (Arnqvist & Rowe, ). Testing if sexual conflict maintains genetic variation in natural populations is a tremendous challenge—it requires both identifying loci that harbor sexually antagonistic alleles and determining whether those alleles are maintained as stable polymorphisms (Mank, ). Doing so genome‐wide is even harder because it is not tractable to identify sexually antagonistic alleles and test for stable polymorphisms at all loci. Dutoit et al. ( ) confront this challenge in a paper published in this issue of Molecular Ecology . Using gene expression and population genomic data from the collared flycatcher, Dutoit et al. ( ) identify associations and correlations between genomic signatures of balanced polymorphisms and sexual conflict.

Genes Relocated Between Drosophila Chromosome Arms Evolve Under Relaxed Selective Constraints Relative to Non-Relocated Genes - Margaret L. I. Hart; Ban L. Vu; Quinten Bolden; Keith T. Chen; Casey L. Oakes; Lejla Zoronjic; Richard P. Meisel (Journal of Molecular Evolution, 2018)

Discrimination of T-cell subsets and T-cell receptor repertoire distribution - Isabell Bretschneider; Michael J. Clemente; Christian Meisel; Manuel Guerreiro; Mathias Streitz; Werner Hopfenmüller; Jaroslav P. Maciejewski; Marcin W. Wlodarski; Hans-Dieter Volk (Immunologic Research, 2014)

GGOS-D: homogeneous reprocessing and rigorous combination of space geodetic observations - M. Rothacher; D. Angermann; T. Artz; W. Bosch; H. Drewes; M. Gerstl; R. Kelm; D. König; R. König; B. Meisel; H. Müller; A. Nothnagel; et al. (Journal of Geodesy, 2011)

Evolutionary Dynamics of Recently Duplicated Genes: Selective Constraints on Diverging Paralogs in the Drosophila pseudoobscura Genome - Richard P. Meisel (Journal of Molecular Evolution, 2009)

Brain antigens in functionally distinct antigen-presenting cell populations in cervical lymph nodes in MS and EAE - Marloes van Zwam; Ruth Huizinga; Marie-José Melief; Annet F. Wierenga-Wolf; Marjan van Meurs; Jane S. Voerman; Knut P. H. Biber; Hendrikus W. G. M. Boddeke; Uta E. Höpken; Christian Meisel; Andreas Meisel; Ingo Bechmann; et al. (Journal of Molecular Medicine, 2009)

Diverse contributing sources to chromitite petrogenesis in the Shebenik Ophiolitic Complex, Albania: evidence from new PGE- and Os-isotope data - H. Kocks; F. Melcher; T. Meisel; K.-P. Burgath (Mineralogy and Petrology, 2007)

Polymorphism of the N -acetyltransferase ( NAT2 ), smoking and the potential risk of periodontal disease - P. Meisel; Ramona Timm; H. Sawaf; Jutta Fanghänel; Werner Siegmund; T. Kocher (Archives of Toxicology, 2000)